Características de patentes de dispositivos para rehabilitación física registradas en los Estados Unidos - Nieto-Gutierrez, Wendy (2019)
ABSTRACT Introduction: Physical rehabilitation can be benefitted from the use of devices, which are usually patented. The United States Patent and Trademark Office (USPTO) is one of the largest and most recognized patent and trademark offices. The characteristics and evolution of patents for physical rehabilitation is of great interest; however, there are few studies in this respect. Objective: To identify the characteristics of patents of physical rehabilitation devices for the physical rehabilitation of damaged limbs registered the United States Patent and Trademark Office. Material and methods: A cross-sectional descriptive study was conducted. A search was made at UPSTO using a list of keywords related to rehabilitation. Ten groups of patents related to rehabilitation were chosen. The variables studied were: patent number, publication date, country, holder, patent area, limbs for which the patent is useful, and portability. A descriptive analysis was performed by using STATA v.14. Results: A total of 1971 patents were analyzed, of which 16.2% were included in the rehabilitation groups and 83.8% in the physical exercise groups. The 36.6% of them were corporate-owned patents, 29.9% were portable, and 46.3% had usability which demonstrated to be useful for both extremities. Conclusions: Of the patents found, those focused on physical exercise were predominant. There is a greater number of useful patents for both extremities. In addition, there is an upward trend over time, the number of patents in the area of ​​rehabilitation, and portable inventions.